Effects of transient and persistent cerebrospinal fluid drainage on sleep disordered breathing in patients with idiopathic adult hydrocephalus syndrome. Issue 4 (1st October 1998) - Kristensen, Bo; Malm, Jan; Rabben, Terje
Abstract : OBJECTIVES: To examine sleep disordered breathing including obstructive sleep apnoea in patients with idiopathic adult hydrocephalus syndrome (IAHS) and to study the effects of CSF drainage and shunting procedure on sleep disordered breathing. METHODS: In 17 patients with IAHS polysomnographic investigations were performed before and after lumbar CSF drainage and after shunt operation. RESULTS: Baseline investigations documented a high prevalence of sleep related obstructive respiratory events (respiratory disturbance index >10 in 65% of the patients) and impaired sleep structure. There was no correlation between respiratory disturbance index and CSF pressure. Minimum oxygen saturation was highly correlated with cognitive function. Neither lumbar CSF drainage nor shunting alleviated the respiratory disturbance index. REM and delta sleep increased initially after shunting but there was no sustained effect on sleep quality. CONCLUSIONS: Sleep disordered breathing is a prevalent finding in patients with IAHS. The shortcoming of CSF drainage to improve sleep disordered breathing either transiently or permanently implies that sleep disordered breathing is a coexistent condition, or an irreversible consequence of the hydrocephalus, with a potential of causing additional dysfunction in IAHS.